2014
DOI: 10.1177/0959651814548440
|View full text |Cite
|
Sign up to set email alerts
|

Friction modelling and simulation at system level: Considerations to load and temperature effects

Abstract: The influence of load and temperature on friction is addressed in a practical way to provide a step forward in simulation-based design through the development and the numerical implementation of realistic system-level models of frictional losses. Hydraulically and electrically supplied actuators are considered at both individual component level (e.g. gear pairs, nut-screws or bearings) and integrated equipment level (e.g. reducers or even complete actuators). The need for more realistic modelling of friction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…In practice, the friction force may vary, not only with the relative velocity and relative displacement of contact surface but also with the load, temperature, wear, and so on. 17 So partial parameters of the LuGre model may be adapted in order to compensate the friction variation caused by the above factors. It is revealed that the adaptations of σ 0 , σ 1 , σ 2 can be responsible for most parameter variations.…”
Section: Composite Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the friction force may vary, not only with the relative velocity and relative displacement of contact surface but also with the load, temperature, wear, and so on. 17 So partial parameters of the LuGre model may be adapted in order to compensate the friction variation caused by the above factors. It is revealed that the adaptations of σ 0 , σ 1 , σ 2 can be responsible for most parameter variations.…”
Section: Composite Controllermentioning
confidence: 99%
“…15,16 In addition, friction is not only dependent on the relative displacement and relative velocity but also related to temperature, load, lubricant, and so on. 17 To deal with the variations of friction model parameters caused by the above factors, some adaptive controllers have been presented. Examples include a smooth adaptive viscous friction compensator using a nonlinear observer based on the Dahl model of friction, 18 and adaptive friction compensation method based on a continuously differentiable friction model for motion control of servo mechanisms prescribed performance.…”
Section: Introductionmentioning
confidence: 99%
“…A precise knowledge of the friction in the system helps to improve the mechatronic design, increase precision, and gain a more accurate simulation. Recently this topic has got increasing attention in research for industrial robots [1]- [3] , but also for lightweight service robots knowledge of friction is advantageous, especially when physical human robot interaction plays a major role.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned demands are not fully covered in the well known static or dynamic friction models [7]- [11]. Current research addresses the importance and the inclusion of temperature, velocity, and load in static friction models [1], [3], [12]- [15]. Since we have trajectories with many reversals and low velocity portions we aim on a dynamic friction model.…”
Section: Introductionmentioning
confidence: 99%
“…Their research was performed under the constant‐speed friction data but it was not a real projection of the situations in which the mechanical and robotic systems could work. Maré studied the effects of the load and temperature on friction and experimentally showed that the friction is strongly influenced by temperature. He proposed a static temperature dependent friction model that was validated for a narrow temperature range.…”
Section: Introductionmentioning
confidence: 99%